The realization of the “Concept of digital transformation, development of the information and communication technologies and cybersecurity industry for 2023‒2029” by implementing blockchain in the technologies of the Republic of Kazakhstan and the prob - Zhamburbayeva, S.; Ilyassova, G.A. (Bulletin of the Karaganda University “Law Series”, 2024)
In the scientific article, the implementation of the “Concept of digital transformation, development of the information and communication technologies and cybersecurity industry for 2023‒2029” was considered, which, according to the authors, is possible through the prism of the introduction of blockchain technologies in the Republic of Kazakhstan. The main focus is on analyzing the current state of the digital infrastructure, identifying potential applications of the blockchain and identifying regulatory issues related to its use. The article begins with an overview of the strategic objectives of the Concept and an assessment of its impact on the economic development of the country. The authors discuss blockchain as an innovative tool capable of ensuring transparency, security and reliability of data in various sectors, including finance, healthcare and public administration. In this aspect, an overview of existing technologies that have already been applied in practice was conducted; accordingly, the Republic of Kazakhstan can adopt them for the future. Special attention is paid to the analysis of the problems faced by Kazakhstan in integrating blockchain technologies into the existing legal system. The authors explore the need to develop new legislative acts, as well as adapt existing regulatory documents to create a favorable legal environment for blockchain. The potential risks and benefits that may arise as a result of the large-scale introduction of blockchain technologies in Kazakhstan are also discussed. In conclusion, the article offers recommendations on improving the legal framework for blockchain, emphasizing the importance of international cooperation and exchange of experience in this area.